2017
DOI: 10.1097/01.aoa.0000521262.72642.4b
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Efficacy of Nonsteroidal Anti-Inflammatory Agents (NSAIDs) in Patients Undergoing Cesarean Deliveries: A Meta-Analysis

Abstract: (Reg Anesth Pain Med. 2016;41(6):763–772) In 2007, there were 1.4 million cesarean deliveries (1 in 3 live births) in the United States alone. Pain after cesarean delivery can be severe in many patients, with 78% of women undergoing cesarean delivery reporting moderate to severe postoperative pain within the first 24 hours postoperatively. Nonsteroidal anti-inflammatory drugs (NSAIDs) are effective in the treatment of this postoperative pain despite them being generally viewed as “weak” analgesics. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
0
12
4
Order By: Relevance
“…Although many studies have concluded that uterine involution causes pain after delivery [20,21], we did not nd that the usage of more than one uterotonic agent promoting additional uterine contraction affected pain. A systematic review showed that the NSAIDs used were better than a placebo and paracetamol for the relief of pain arising from uterine cramping [20].…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Although many studies have concluded that uterine involution causes pain after delivery [20,21], we did not nd that the usage of more than one uterotonic agent promoting additional uterine contraction affected pain. A systematic review showed that the NSAIDs used were better than a placebo and paracetamol for the relief of pain arising from uterine cramping [20].…”
Section: Discussioncontrasting
confidence: 75%
“…A systematic review showed that the NSAIDs used were better than a placebo and paracetamol for the relief of pain arising from uterine cramping [20]. Furthermore, NSAIDs have been reported to have an opioid-sparing effect after cesarean delivery [21]. Nevertheless, our study failed to demonstrate the effects of NSAIDs on postcesarean section pain.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…An American College of Obstetricians and Gynecologists committee opinion summary, 11 in addition to a consensus statement from the Society of Obstetric Anesthesia and Perinatology 12 and Enhanced Recovery After Surgery Society guidelines, 13e15 has published recommendations that address some of the poorly performing ObsQoR-10 items identified in this study, such as pain associated with cesarean delivery. These recommendations endorse the evidence-based use of long-acting intrathecal opioids, 16 regular acetaminophen, 17 and nonsteroidal antiinflammatory drugs 18 as part of a multimodal analgesia regimen aiming to reduce the need for systemic or parenteral opioids in the postpartum period. Despite the study institution adhering to these recommendations, pain was still consistently the worst…”
Section: Original Researchmentioning
confidence: 99%
“…Multiple studies have shown the opioid-sparing effects of these agents independently. [35][36][37] Further studies have even shown additional analgesic effects when acetaminophen and NSAIDs are combined. 38,39 In our cohort, patients received combination pills containing both an opioid and acetaminophen 81% of the time, as opposed to opioid-only pills.…”
Section: Discussion Key Findingsmentioning
confidence: 99%